2014
DOI: 10.1523/jneurosci.0538-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin Attenuates Serotonin-Induced Long-Term Synaptic Facilitation by Phosphorylation of p38 Mitogen-Activated Protein Kinase

Abstract: Doxorubicin (DOX) is an anthracycline used widely for cancer chemotherapy. Its primary mode of action appears to be topoisomerase II inhibition, DNA cleavage, and free radical generation. However, in non-neuronal cells, DOX also inhibits the expression of dual-specificity phosphatases (also referred to as MAPK phosphatases) and thereby inhibits the dephosphorylation of extracellular signal-regulated kinase (ERK) and p38 mitogen-activated protein kinase (p38 MAPK), two MAPK isoforms important for long-term memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 64 publications
3
50
0
Order By: Relevance
“…DOX induced reduction in brain 5‐HT, DA, and NE accompanied with significant elevation of CHE activity. The observed results confirmed by Liu et al . showed that treatment by DOX blocked 5‐HT activity.…”
Section: Discussionmentioning
confidence: 99%
“…DOX induced reduction in brain 5‐HT, DA, and NE accompanied with significant elevation of CHE activity. The observed results confirmed by Liu et al . showed that treatment by DOX blocked 5‐HT activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, hyperactivation of ERK signaling may lead to detrimental effects on cognition consistent with our results that ERK 1/2 is activated in OVX rats treated with chemotherapeutic agents. A recent study found that doxorubicin exposure in both rat cortical neurons and Aplysia sensory neurons induced the activation of ERK and p38 MAPK [44]. It is also possible that the differential activation of these MAPK isoforms may ultimately influence synaptic plasticity through the regulation of the transcriptional repressor CREB2 [44].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that doxorubicin exposure in both rat cortical neurons and Aplysia sensory neurons induced the activation of ERK and p38 MAPK [44]. It is also possible that the differential activation of these MAPK isoforms may ultimately influence synaptic plasticity through the regulation of the transcriptional repressor CREB2 [44]. Both pathways have sites where they can intersect.…”
Section: Discussionmentioning
confidence: 99%
“…DOX concentrations used in vitro vary widely (0.5 to 20 μM) 12, 45, 46, 59, 60 . However, in vivo measurement of the amount of DOX in rodent brain after intraperitoneal injection is approximately 0.25 μM 11 .…”
Section: Methodsmentioning
confidence: 99%